Peningkatan kemampuan Berpikir Kritis Matematis dan Self-Efficacy dengan Menggunakan Pendekatan Pembelajaran Creative Problem Solving - Tista Imam Riyadi (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2021)
This study aims to determine the differences of Critical Thinking mathematically attainment and enhancement between students who get Creative Problem Solving (CPS) learning approach to those who get conventional learning in terms of the whole students and based The Ability of Early Mathematical (AEM). Type of this research is a quasi-experimental. The sample research is obtained by using purposive random sampling technique, it is applied to two classes of the first grade of SMAN 1 Jakarta. The first class gets approach Creative Problem Solving and the second class gets conventional learning model (PC). All class are given a pre-test and post-test of critical thinking mathematically. The results showed that (1) the students of CPS have greater ability of mathematically critical thinking rather than those of PK, (2) the the students of CPS class have greater ability of mathematically critical thinking enhancement rather than of PC ; (3) different points of mathematically critical thinking enhancement appear in CPS class (level of students of AEM); it occurs between medium and low level, high and low level, but the difference is not found in the high and medium level, (4) difference of mathematically critical thinking enhancement occurs in PCPS and PC class based their Ability of Early Mathematical (AEM), (5) mathematical Self-Efficacy enhancement of the CPS students seems better than the conventional ones; (6) mathematical Self-Efficacy enhancement differs in PCPS class based on AEM (high, medium, and low). Keywords: Approach of Learning Creative Problem Solving, Mathematical Critical Thinking, and Self-Efficacy